EFFECTIVE USE OF HUMAN CAPITAL IN THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Inamov Farhodjon Ikrom o'g'li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the improvement of efficiency based on the effective use of human capital in the development of small business and private entrepreneurship is studied, and the goals and main directions of its further development are indicated. In addition, a scientific proposal and conclusions were given in this regard.